2021
DOI: 10.3390/su13063198
|View full text |Cite
|
Sign up to set email alerts
|

Synthesizing Multi-Layer Perceptron Network with Ant Lion Biogeography-Based Dragonfly Algorithm Evolutionary Strategy Invasive Weed and League Champion Optimization Hybrid Algorithms in Predicting Heating Load in Residential Buildings

Abstract: The significance of accurate heating load (HL) approximation is the primary motivation of this research to distinguish the most efficient predictive model among several neural-metaheuristic models. The proposed models are formulated through synthesizing a multi-layer perceptron network (MLP) with ant lion optimization (ALO), biogeography-based optimization (BBO), the dragonfly algorithm (DA), evolutionary strategy (ES), invasive weed optimization (IWO), and league champion optimization (LCA) hybrid algorithms.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 131 publications
0
14
0
Order By: Relevance
“…To verify the effectiveness of GCLPSO on multi-threshold image segmentation, GCLPSO will be compared with CLPSO, two improved algorithms SCADE and m_SCA, and three original algorithms SSA, SCA, and SMA, respectively. To ensure the validity and fairness of the experiments (Chen et al, 2021 ; Moayedi and Mosavi, 2021d ; Nosratabadi et al, 2021 ; Yang et al, 2021 ), all the algorithms involved in the comparisons were conducted under the same experimental conditions. Such a setting is one of the most crucial rules in the artificial intelligence community (Song et al, 2020 ; Thaher et al, 2020 ; Mousavi et al, 2021 ; Tavoosi et al, 2021 ).…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…To verify the effectiveness of GCLPSO on multi-threshold image segmentation, GCLPSO will be compared with CLPSO, two improved algorithms SCADE and m_SCA, and three original algorithms SSA, SCA, and SMA, respectively. To ensure the validity and fairness of the experiments (Chen et al, 2021 ; Moayedi and Mosavi, 2021d ; Nosratabadi et al, 2021 ; Yang et al, 2021 ), all the algorithms involved in the comparisons were conducted under the same experimental conditions. Such a setting is one of the most crucial rules in the artificial intelligence community (Song et al, 2020 ; Thaher et al, 2020 ; Mousavi et al, 2021 ; Tavoosi et al, 2021 ).…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Heuristic pdf method Ant-lion optimization [42] coyote optimizer [43] Modified sine-cosine algorithm [44] Particle swarm optimization [45] From Tables 2-7, it is observed that the selection of DGs location is better found under GA for CPLF and CILF in comparison to other methods. By comparing the real power loss, sensitivity, and accuracy, it can be concluded that bus 17 is the best location for the placement of DG for both CPLF and CILF.…”
Section: Ga Methodsmentioning
confidence: 99%
“…Figures 6 and 7 provide the performance parameter comparison of GA with the heuristic method at different buses for CPLF and CILF. Moreover, in order to have comprehensive analysis and comparison for the DG location with GA and heuristic pdf, the results are compared with those obtained with the ant-lion optimization algorithm [42], coyote optimizer [43], modified sine-cosine algorithm [44], and particle swarm optimization [45]. The performance parameter evaluation for the estimation of DG location by using the ant-lion optimization algorithm [42], coyote optimizer [43], modified sine-cosine algorithm [44], and particle swarm optimization [45] is shown in Tables 4-7 for CPLF and CILF type of load.…”
Section: Genetic Algorithmmentioning
confidence: 99%
See 2 more Smart Citations